Use it or lose it? Identifying reasons for the low use of psychosocial support by hospital staff - Frank van de Baan; Lieze Poesen; Daan Westra; Bram Fleuren; Dirk Ruwaard; Fred Zijlstra; Rachel Gifford (BMC, 2023)
Abstract Background Psychosocial support programs are a way for hospitals to support the mental health of their staff. However, while support is needed, utilization of support by hospital staff remains low. This study aims to identify reasons for non-use and elements that are important to consider when offering psychosocial support. Methods This mixed-method, multiple case study used survey data and in-depth interviews to assess the extent of psychosocial support use, reasons for non-use and perceived important elements regarding the offering of psychosocial support among Dutch hospital staff. The study focused on a time of especially high need, namely the COVID-19 pandemic. Descriptive statistics were used to assess frequency of use among 1514 staff. The constant comparative method was used to analyze answers provided to two open-ended survey questions (n = 274 respondents) and in-depth interviews (n = 37 interviewees). Results The use of psychosocial support decreased from 8.4% in December 2020 to 3.6% by September 2021. We identified four main reasons for non-use of support: deeming support unnecessary, deeming support unsuitable, being unaware of the availability, or feeling undeserving of support. Furthermore, we uncovered four important elements: offer support structurally after the crisis, adjust support to diverse needs, ensure accessibility and awareness, and an active role for supervisors. Conclusions Our results show that the low use of psychosocial support by hospital staff is shaped by individual, organizational, and support-specific factors. These factors can be targeted to increase use of psychosocial support, whereby it is important to also focus on the wider hospital workforce in addition to frontline staff.